Reconsidering the “War on Rats”: What We Know From Over a Century of Research Into Municipal Rat Management - Lee, Michael J.; Byers, Kaylee A.; Stephen, Craig; Patrick, David M.; Corrigan, Robert; Iwasawa, Stefan; Himsworth, Chelsea G. (Frontiers in Ecology and Evolution, 2022)
To sustainably control urban rat infestations, management efforts need to encompass large areas of urban centers. Therefore, the objective of this review and narrative synthesis was to collate what is known about municipal-scale rat management. We explored the management frameworks that have been used at a large scale in cities and we describe the expectations of experts who have designed and implemented these frameworks. We found that there has been a persistent “war on rats” paradigm driving this literature since the early 1900s. Not only was there little quantitative evidence to support this paradigm and associated methodologies, but together, they failed to meet the expectations of those who designed and implemented them due to real-world constraints (i.e., limited resources). To improve the field of municipal management, we identify two distinct options. First, stakeholders may continue to wage the “war on rats” while improving existing strategies within this paradigm. Key pathways forward include developing evaluation metrics aligned with program objectives, establishing the cost-effectiveness of methodologies, and improving control efficacy. Second, we suggest a new paradigm, one that considers that rat management is a complex system that must be approached by first mapping its complexity to highlight and prioritize the many complex upstream determinants of infestations. This perspective highlights how rat management may be a wicked problem for which there is no overarching solution and instead can only be managed by making incremental gains in individual components of the problem over time. Importantly, we propose an alternative management objective that places a priority on improving the overall health of the community, instead of on eliminating rats, and we stress that management goals must address stakeholders’ goals as their investment is essential for a sustained program.